An Analysis of Violation of Cooperative Principle in Alice in Wonderland Movie Script - Serlin Serlin; Ela Martisa (ELITE: Journal of English Language and Literature, 2017)
This research aims at analyzing the violating of cooperative principles presented in the â€œAlice in Wonderlandâ€ movie script. This research used the descriptive qualitative method. The data were taken from the utterances among the characters in the â€œAlice in Wonderlandâ€ movie script. The data were collected by searching and downloading the movie, watching the movie, reading the movie script, coding the data, re-watching, and re-reading, capturing of image and data reduction. The method of analyzing data consists of presenting the data into conversation and image, describing the data, interpreting data, and making conclusions to answer the research questions. The result of this research shows there are 18 violations of the maxims, they are: the violating maxim of quantity is 8 data, it happens because the speaker gives excessive or little information; the violating maxim of quality is 4 data, it happens because the speaker gives untruth information or say something lie; the violating maxim of relevance are 4 data, it happens because the speaker gives irrelevant information; the violating maxim of manner are 2 data, it happens because the speaker gives unclear or ambiguous information. The most violated maxim is the maxim of quantity.